2020
DOI: 10.3389/fimmu.2020.01054
|View full text |Cite
|
Sign up to set email alerts
|

The Multifaceted Function of Granzymes in Sepsis: Some Facts and a Lot to Discover

Abstract: Sepsis is a serious global health problem. In addition to a high incidence, this syndrome has a high mortality and is responsible for huge health expenditure. The pathophysiology of sepsis is very complex and it is not well-understood yet. However, it is widely accepted that the initial phase of sepsis is characterized by a hyperinflammatory response while the late phase is characterized by immunosuppression and immune anergy, increasing the risk of secondary infections. Granzymes (Gzms) are a family of serine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 110 publications
0
40
0
Order By: Relevance
“…We found that CXCL11 was positively correlated with CCL4, CCL5, CXCL9, and CXCL10 in COAD, which are associated with DC, NK, and T cell recruitment and play important roles in inhibiting tumor growth and improving prognosis ( Böttcher et al, 2018 ; Cabrero-de, Las Heras and Martínez-Balibrea, 2018 ). Accordingly, we found positive correlations between CXCL11 and cytotoxic genes (IFNG, GZMA, GZMB, GZMK, and GZMM), which were validated to enhance the cytotoxic function by other immunocytes and contribute to the immunostimulatory microenvironment ( Garzón-Tituaña et al, 2020 ). These data indicate that CXCL11 promotes antitumor immunity by mediating the infiltration of immunocytes.…”
Section: Discussionmentioning
confidence: 76%
“…We found that CXCL11 was positively correlated with CCL4, CCL5, CXCL9, and CXCL10 in COAD, which are associated with DC, NK, and T cell recruitment and play important roles in inhibiting tumor growth and improving prognosis ( Böttcher et al, 2018 ; Cabrero-de, Las Heras and Martínez-Balibrea, 2018 ). Accordingly, we found positive correlations between CXCL11 and cytotoxic genes (IFNG, GZMA, GZMB, GZMK, and GZMM), which were validated to enhance the cytotoxic function by other immunocytes and contribute to the immunostimulatory microenvironment ( Garzón-Tituaña et al, 2020 ). These data indicate that CXCL11 promotes antitumor immunity by mediating the infiltration of immunocytes.…”
Section: Discussionmentioning
confidence: 76%
“…Nevertheless, even where DNAm proxies CRP and IL6 correlate ~0.2 with measured protein levels, they provide a more stable measure of expression than proteomic measures when averaged longitudinally; they often outperform the measured proteins in relation to associations with health outcomes and lifestyle factors [13][14][15] . As with CRP and IL6, many of the proteins we have created proxies for are involved in or associated with the acute-phase response; GZMA is thought to promote the release of IL6, IL8 and TNF-alpha, thereby inducing a cytokine syndrome in those with sepsis (a condition hallmarked by a rapid alterations in the inflammatory state) 11,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated the involvement of Gzm in the pathophysiology of sepsis ( 35 ). GzmA, B, K and M can stimulate the production, release and/or processing of several cytokines ( 6 ).…”
Section: Discussionmentioning
confidence: 99%